2017
DOI: 10.22246/jikm.2017.38.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gwaruhaengryeon-hwan on COPD and Particulate Matter Induced Lung Injury on a Mouse Model

Abstract: Chronic obstructive pulmonary disease (COPD), which is characterized by airway obstruction, leads to, as the two major forms of COPD, chronic bronchitis and emphysema. This study was conducted to evaluate the effects of herbal formula, PM014, in a murine model of COPD. Balb/c mice were treated once with each herb extract in PM014 or PM014 mixture via an oral injection. Lipopolysaccharide (LPS) or elastase/LPS were administrated to the mice to induce a disease that resembles COPD. PM014 treatment significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…GHX02 was formed by adding Scutellariae Radix to GRHRH. GRHRH already demonstrated its anti-inflammatory effects on COPD and particulate matter induced lung injury on a mouse model 16) and previous studies reported that Scutellariae Radix inhibits the production of several inflammatory cytokines 18) and has antioxidant effects 19) .…”
Section: Introductionmentioning
confidence: 97%
“…GHX02 was formed by adding Scutellariae Radix to GRHRH. GRHRH already demonstrated its anti-inflammatory effects on COPD and particulate matter induced lung injury on a mouse model 16) and previous studies reported that Scutellariae Radix inhibits the production of several inflammatory cytokines 18) and has antioxidant effects 19) .…”
Section: Introductionmentioning
confidence: 97%
“…Here, we tried to expand the effect by adding a herb ( Scutellariae radix) with a similar therapeutic mechanism. Gwaruhaengryeon-hwan demonstrated its anti-inflammatory effects on COPD and particulate matter-induced lung injury in a mouse model ( Lee et al, 2017 ). Scutellariae radix has also been reported to inhibit the production of several inflammatory cytokines ( Kim et al, 2015 ) and have antioxidant effects ( Guo et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…질환이다 1 6 에 따라 살펴보면 풍한형(風寒 型)의 소청룡탕 7 , 폐열형(肺熱型)의 과루행련환 유 래 GHX02 8 , 담탁형(痰濁型)의 사간탕 유래 SGX01 9 , 폐허형(肺虛型)의 감길탕 유래 GGX 10 , 신음허형 (腎陰虛型)의 청상보하탕 유래 PM014 11 등이 있었 으나 COPD에 병발하는 근감소에 대한 영향을 동 시에 평가한 연구는 찾기 어려웠다. 쌍화탕(雙和湯)은 ≪동의보감(東醫寶鑑)≫ 12 에서 정신과 신체가 피로하고 기혈이 모두 손상되었을 때 사용하는 것으로 기재된 처방으로 사물탕(四物 湯)과 황기건중탕(黃耆建中湯)의 합방으로 구성되 어 있으며 13 , 항피로 14 , 면역활성화 15 에 대한 효능 연 구와 운동수행능력 16 , 만성피로 17 기기는 열탕추출기(Daewoong, Korea), rotary vacuum evaporator(Buchi, Switzerland), freeze dryer (EYELA, Japan), CO2 incubator(Forma Scientific, USA), micro-pipet(Gilson, France), clean bench(Vision Scientific, Korea), autoclave(Sanyo, Japan), water bath(Vision scientific, Korea), Biosystem XA(Buxco Research System, USA), vortex mixer(Vision scientific, Korea), spectrophotometer(Shimazue, Japan), thermocycler system(MWG Biotech, Germany), deep-freezer(Sanyo, Japan), centrifuge(Sigma, USA), homogenizer(OMNI, USA), plate shaker(Lab-Line, USA), ELISA reader (Molecular Devices, USA), ice-maker(Vision scientific, Korea) 및 chemical balance(Cas, Korea) 등을 사 용하였다.…”
unclassified